Sevelamer Attenuates Bioprosthetic Heart Valve Calcification - Meng, Zhen; Li, Zhe; Zhang, Erli; Zhang, Li; Liu, Qingrong; Wu, Yongjian (Frontiers in Cardiovascular Medicine, 2021)
Objective: Sevelamer hydrochloride is a phosphate binder used for the treatment of hyperphosphatemia in CKD patients which can reduce the valvular and vascular calcification. The aim of the study was to examine the effects of sevelamer treatment on calcification in bioprosthetic heart valves (BHVs). Methods: Wister rats were randomly divided into 3 groups according to sevelamer intake and implantation (sham-sham operation; implant-implantation and normal diet, implant+S- implantation and sevelamer diet). 2 kinds of BHVs (BP treated with glutaraldehyde (GLUT) or non-GLUT technique) were implanted in rat dorsal subcutis at 4 weeks. After implantation, sevelamer was administered to implant+S group. Animals are executed at 0(immediately after implantation),7,14,28,56 days. Calcium levels were determined by atomic absorption spectroscopy and von kossa staining. Serum biochemistry analysis, western bloting, real-time qPCR, ALP activity measurement, histopathologic analysis and ELISA were conducted to identify the anti-calcification mechanism of sevelamer. Result: non-GLUT crosslinking attenuates BHVs calcification. serum phosphate and calcium were unreacted to sevelamer after 14 days treatment. However, the mean calcium level of the non-GLUT BHVs in implant+S group decreased significantly in 56 days. PTH level, Inflammatory cell infiltration, systematic and local inflammation and expression of BMP2, RUNX2, ALP, IL-1β, IL-6 and TNF-α were significant reduced in the implant+S group. Conclusion: sevelamer treatment significantly attenuated the calcification of BHVs and had anti-inflammation effects which are independent from serum calcium and phosphate regulation. Thus, sevelamer treatment might be helpful for the longevity of BHVs